Gender Segregation Across Engineering Majors: How Engineering Professors Understand Women's Underrepresentation in Undergraduate Engineering. Issue 1 (2nd January 2017) - Blosser, Emily
ABSTRACT: Women's persistent underrepresentation in undergraduate engineering is a well-documented concern. One issue missing from many discussions on the topic, however, is that women are not equally underrepresented in all engineering majors. Furthermore, a significant portion of the research focuses solely on women's experiences within engineering. We know far less about how key stakeholders, such as faculty, understand gender stratification in engineering education. Faculty are influential figures who have been shown to play a central role in introducing students to the profession and can significantly impact students' experiences. This article addresses these gaps by examining the reasons engineering professors provide to explain women's underrepresentation across majors. Using data from 23 in-depth interviews at one university, the findings demonstrate how the majority of faculty mobilize gendered images to position some majors as feminine and others as masculine, and then suggest that this impacts women's choices of fields. Chemical engineering, however, served as an interesting case in this study because it was described as gender diverse. These findings contribute to discussions about the construction of gendered cultures within engineering and show how engineering faculty play a role in this process.